Social Fiqh Integration in Hadith Interpretation and Contemporary Islamic Law - Arina Nur Fathimah; Isnaini Lu’luatim Muthoharoh (Academia Open, 2026)
General Background Social Fiqh represents a progressive paradigm in Islamic legal thought that seeks to align jurisprudence with evolving social realities. Specific Background Developed by Kiai Sahal Mahfudh, Social Fiqh emphasizes the integration of textual and contextual approaches grounded in maqasid al-shari’ah, while hadith studies have historically been dominated by textual and authenticity-focused methods. Knowledge Gap Despite extensive discussions on Social Fiqh and hadith methodology, limited studies elaborate their integration as a unified interpretative framework. Aims This study aims to examine the methodology of Social Fiqh and integrate it with methods of hadith understanding to construct a contextual interpretative approach. Results The findings demonstrate that Social Fiqh reorients hadith interpretation by prioritizing contextualization, public welfare (maslahah), and methodological reasoning, shifting from rigid textualism to a dynamic, socially responsive framework. It highlights reinterpretation of texts, transformation from textual to methodological adherence, and alignment with socio-cultural realities. Novelty This study offers a conceptual synthesis that positions Social Fiqh as a hermeneutical tool for hadith interpretation, bridging normative Islamic texts with contemporary social contexts. Implications The integration supports a flexible yet principled application of Islamic law, reinforcing its relevance in modern society while maintaining adherence to foundational sharia values. Highlights: Context-based reasoning connects classical teachings with present societal conditions. Methodological shift replaces rigid legal formulations with adaptive analytical processes. Welfare-oriented principles guide reinterpretation of religious texts in modern settings. Keywords: Method of Hadith Undestanding, Fiqh Sosial, Contextualualization